2015
DOI: 10.1038/srep09211
|View full text |Cite
|
Sign up to set email alerts
|

Detection of BRAF mutation in Chinese tumor patients using a highly sensitive antibody immunohistochemistry assay

Abstract: BRAF mutations can be found in various solid tumors. But accurate and reliable screening for BRAF mutation that is compatible for clinical application is not yet available. In this study, we used an automated immunohistochemistry (IHC) staining coupled with mouse monoclonal anti-BRAF V600E (VE1) primary antibody to screen the BRAF V600E mutation in 779 tumor cases, including 611 colorectal carcinomas (CRC), 127 papillary thyroid carcinomas (PTC) and 41 malignant melanomas. Among the 779 cases, 150 cases were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 24 publications
(24 reference statements)
3
30
0
Order By: Relevance
“…However, studies from molecular diagnostic laboratory in our center also revealed low incidence of BRAF V600E mutations in Chinese CRCs detected by the high sensitive testing of ARMS PCR or next‐generation sequencing . In previous study, we also had confirmed that the fully automated IHC method to detect BRAF V600E mutation in CRCs had a high specificity and sensitivity validated by high sensitive ARMS PCR . So, IHC on BRAF V600E should not be the systematic shortcoming causing low rate of the mutation.…”
Section: Discussionmentioning
confidence: 54%
“…However, studies from molecular diagnostic laboratory in our center also revealed low incidence of BRAF V600E mutations in Chinese CRCs detected by the high sensitive testing of ARMS PCR or next‐generation sequencing . In previous study, we also had confirmed that the fully automated IHC method to detect BRAF V600E mutation in CRCs had a high specificity and sensitivity validated by high sensitive ARMS PCR . So, IHC on BRAF V600E should not be the systematic shortcoming causing low rate of the mutation.…”
Section: Discussionmentioning
confidence: 54%
“…In particular, considering the study of Qiu et al [23], who instead used the same fully automatized immunohistochemical method as we did, they found that the sensitivity and specificity of the VE1 antibody were 100 and 99%, respectively. However, it is to consider that in their set there were only 41 cases of malignant melanoma while the majority of them were colorectal carcinomas (611 samples) and papillary thyroid carcinomas (127 specimens) [23].…”
Section: Discussionmentioning
confidence: 81%
“…In particular, considering the study of Qiu et al [23], who instead used the same fully automatized immunohistochemical method as we did, they found that the sensitivity and specificity of the VE1 antibody were 100 and 99%, respectively. However, it is to consider that in their set there were only 41 cases of malignant melanoma while the majority of them were colorectal carcinomas (611 samples) and papillary thyroid carcinomas (127 specimens) [23]. Our results are close to those of Yaman et al [24], who, in a study on 48 cases with both primary cutaneous and metastatic melanoma using the fully automatized Ventana® immunohistochemical method with the addition of an amplification signaling kit, reached a positive predictive value of 98.2% and a negative predictive value of 89.7%.…”
Section: Discussionmentioning
confidence: 81%
“…This includes LS screening for patients meeting the revised Bethesda criteria and for prognostication in patients with stage II (pT3N0 and pT4N0) or above CRC. The reference standard which the Idylla (index test) was compared against is a commonly used standard-care test, the Cobas 4800 BRAF V600 Mutation Test performed on the Cobas 4800 System (Roche Molecular Diagnostics),12 which has been previously validated on CRC tissue and is now in widespread use 17. This assay largely detects the V600E mutation, with limited D or K mutation coverage 12…”
Section: Introductionmentioning
confidence: 99%